Impact and effectiveness of childhood varicella vaccine program in Queensland, Australia. Issue 27 (14th June 2017) - Sheridan, Sarah L.; Quinn, Helen E.; Hull, Brynley P.; Ware, Robert S.; Grimwood, Keith; Lambert, Stephen B.
Abstract: Background: In November 2005, Australia introduced a publicly funded single dose of varicella vaccine for children aged 18-months. We describe the impact of this program on varicella hospitalisations in Queensland and provide the first assessment of single-dose varicella vaccine effectiveness in Australia since the program commenced. Methods: Age-standardised varicella hospitalisation rates were calculated for 2000–2014 and pre- and post-public funding period rates compared. Case-control studies were conducted to investigate the association between vaccine receipt and both varicella hospitalisations and uncomplicated varicella emergency department presentations. Cases were matched to controls from a population-based register by date of birth and state of residence. Vaccine effectiveness was calculated as (1 – odds ratio) × 100%. Results: Compared to the pre-funded period (2000–2003), age-standardised varicella hospitalisation rates declined by more than 70% in 2011–2014 with varicella principal diagnosis rates declining from 5.7 to 1.6 per 100, 000 population per year. Varicella vaccine effectiveness at preventing hospitalisation with a principal diagnosis of varicella among children aged 19-months to 6-years was 81.9% (95% confidence interval: 61.8–91.4%), while for emergency department presentations among children aged 19-months to 8-years it was 57.9% (95% confidence interval: 48.5–65.5%). Conclusions: In Australia, the single-dose varicella vaccination program has substantially reduced varicella morbidity. The single-dose varicella vaccine schedule is moderately-to-highly effective against hospitalisation, but appears less effective against emergency department presentations.